Penerapan Jantanisasi Ikan Nila (Oreochromis niloticus) di Kelompok Tani Kahayan Mina Kelurahan Pahandut Seberang Kecamatan Pahandut Kota Palangka Raya - Ummi Suraya; Muhamad Noor Yasin; Mohamad Rozik (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Community Service program Kahayan Mina fish farmers group in Pahandut Seberang Village, Pahandut Subdistrict, Palangka Raya City in the form of an effort to implement masculinization cultivation technology on tilapia (Oreochromis niloticus) in soil ponds with the aim of increasing the knowledge and skills of target audiences and their benefits. New micro for target partners. Method of activity with the purpose of direct participant observation and interviews, training, technical guidance and demonstration plot demonstration area. The results of the Community Service program in the Kahayan Mina fish cultivator group in cultivating Tilapia in the soil pool can understand and know the tilapia fish maintenance techniques with a maleization/masculinization system.